Teachers as creators of social contexts for scientific learning: New approaches for teacher education - Morais, Ana (2006)
The study continues research developed by the ESSA Group (Sociological Studies of the Classroom) within the field of teacher education. Bernstein’s theory of pedagogic discourse has provided the main conceptual framework and the concept of specific coding orientation has been used to evaluate the professional development of teachers involved in in-service teacher education programmes. The objective of this paper is to present what has been done to appreciate teachers’ professional development in terms of recognition and realisation rules (specific coding orientation) to contexts of pedagogic intervention, discussing the meaning of that relation and the potentialities and limitations of the methodological instruments which have been constructed to evaluate teachers’ performance. A detailed and grounded description of the instruments is given, referring the theoretical and methodological assumptions that have guided their conception and application and giving examples to show how the analysis of the data was done. It is also discussed the extent to which the results of the application of these instruments can give suggestions for a progressive improvement of the external language of description developed in the context of teacher education.